A cross‐sectional survey to explore the prevalence and causes of occupational burnout syndrome among perioperative nurses in Saudi Arabia. Issue 1 (4th October 2020) - Almodibeg, Bader Ali; Smith, Hazel
Abstract: Aim: To detect the level of burnout and its most significant causes among perioperative nurses. Design: A descriptive quantitative cross‐sectional survey design. Methods: Data on burnout and its most significant causes were collected by surveying 39 perioperative nurses in a regional hospital in Saudi Arabia using the Maslach Burnout Inventory and a self‐developed questionnaire. Descriptive statistics were used to perform statistical analysis. Results: Burnout was detected in 5% of respondents. A high level of emotional exhaustion was detected in 87.2%. Similarly, a high level of depersonalization was detected in 56.4%, while 15.4% of nurses showed a low sense of personal accomplishment. Several factors were identified as the causes of burnout such as high workload, staff shortage, poor teamwork, insufficient salary and occupational hazards. However, lack of departmental support and undesirable supervision in the workplace seem to be the main causes of burnout.